ULAR TANGGA SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR IPS PADA PESERTA DIDIK SDI WATUJARA - Adi Neneng Abdullah; Chatarina Novianti (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
The results of initial observations conducted by researchers at Watujara Elementary School, East Ende District, Ende Regency, on the social studies learning process showed that: Teachers still dominate learning so that interactions only occur one way. Second, the low strategy in utilizing learning has an impact on reducing students' concentration and attention in learning. Third, learning is teacher-centered, with a lecture learning model for social studies learning, especially in grade V. Fourth, teachers do not explore students' potential. Fifth, learning activities do not stimulate students to learn actively. Fourth, the classroom atmosphere is less pleasant. This has an impact on students' interest in learning and low learning outcomes. Therefore, improvements are needed, namely by implementing the snake and ladder game media. This research is a Classroom Action Research (CAR). Data collection techniques use observation techniques, questionnaires, tests, documentation, and field notes. The collected data are analyzed descriptively qualitatively and descriptively quantitatively. The results of the study indicate that the snake and ladder game media can increase interest in learning and learning outcomes. This can be seen from the percentage of student learning interest observations that reached the moderately active and very active categories, from 51% in Cycle I to 90% in Cycle II. The percentage of student learning interest questionnaires that reached the moderately interested and very interested categories increased from 60% in Cycle I to 85% in Cycle II. Learning outcomes also increased from 54% in Cycle I to 100% in Cycle II.